The development of embedded band-stop filter for vibration control of a flexible manipulator - Noor Hazreen, Sutomoh (2009)
This project presents an investigation into development of feed forward control scheme for vibration control of a flexible manipulator using band-stop (IIR) filter technique using Xilinx (Spartan 3E) . A constrained planar single-link flexible manipulator is considered in this project and the dynamic model of the system is derived using assumed mode method. A bang-band torque input signal is used to determine the characteristic parameters for designed and evaluate for vibration control technique. The band-stop filter algorithm is designed with sampling frequency of 1000 Hz and cut off frequency between 10 Hz to 300 Hz. After that, it is embedded in Field Programmable Gate Array board using Xilinx software. This algorithm is then applied to the flexible manipulator in the Simulink through PCI 1710 HG DAQ Card. The experimental results presented in time and frequency domain. The effects of the filter order in band-stop performance are also investigated. Finally, a simulation of band-stop filter is compared to the embedded filter onto FPGA board.